Identification of an intermediate for 1,8-dihydroxynaphthalene-melanin synthesis in a race-2 isolate of Fulvia fulva (syn. Cladosporium fulvum) - Medina, Rocío (2018)
Fulvia fulva (syn. Cladosporium fulvum, Mycosphaerellaceae) is a dematiaceous fungus that causes tomato leaf mould. It is characterized by its biotrophic lifestyle and the synthesis of the bianthraquinone secondary metabolite, cladofulvin. The aim of the study was to characterize the dark pigment photochemically synthesized by F. fulva and to elucidate its biochemical pathway. We isolated a black pigment from in vitro cultures of the fungus. We determined the pigment to be 1,8-dihydroxynaphthalene (DHN)-melanin based on its chemical and photochemical characteristics, as well as the presence of flaviolin, when fungal reductases were inhibited by tricyclazole. Furthermore, the pks1 gene involved in pigment synthesis has a KS domain already associated with DHN-melanin. Our findings support the relevance of studying melanization in F. fulva.